The integration of stock exchanges: The case of the Latin American Integrated Market (MILA) and its impact on ownership and internationalization status in Colombian brokerage firms - Beatriz Yepes-Rios; Kelly Gonzalez-Tapia; Maria Alejandra Gonzalez-Perez (Journal of Economics, Finance and Administrative Science, 2015)
This paper describes the changes in ownership and internationalization of the brokerage firms in Colombia as a result of the regional integration process of its stock exchange market through the Latin American Integrated Market (MILA). It proposes that the integration of stock exchanges generated transformations within the brokerage sector, and affected companies in response pursue different strategies to remain competitive in the current state of affairs. In the case of Colombia, stock exchange integration through MILA has resulted into mergers between local brokerage firms, acquisitions from both national and international companies and changes in ownership. – – Este artículo describe los cambios de titularidad y la internacionalización de las compa\~nías de corretaje colombianas, como resultado del proceso de integración regional de su mercado bolsista, a través del Mercado Integrado Latinoamericano (MILA). El documento propone que la integración de las bolsas ha generado transformaciones dentro del sector de los corretajes y que, en respuesta, las empresas afectadas persiguen diferentes estrategias para seguir siendo competitivas dentro de la situación actual de los negocios. En el caso de Colombia, la integración de la bolsa a través del MILA ha originado fusiones entre los corretajes locales, adquisiciones por parte de empresas nacionales e internacionales y cambios de titularidad.
Keywords: F15; 330; Integration; Stock exchanges; Brokerage firms; Capital markets; Latin American Integrated Market; Integración; Bolsas de valores; Compa\~nías de corretaje; Mercados de capital; Mercado Integrado Latinoamericano